Catalytic pyrolysis of washed empty fruit bunch (EFB) using Copper Oxide (CuO) catalyst - Nurul Nadia Mohamed Supian (School of Bioprocess Engineering, University Malaysia Perlis, 2011)
Empty fruit bunch (EFB) is a major solid biomass waste from palm oil industry. Pyrolysis of EFB is thermal decomposition of biomass that occurs in the absence of oxygen. Pyrolysis products consist of bio - oil, char and gas. With addition of copper oxide (CuO) as catalyst, bio - oil yield is increased. The Design Expert software was used to screen active parameters involve in this study pyrolysis temperature, holding time and catalytic or non - catalytic reaction. Catalytic pyrolysis of EFB was carried out in a fixed bed catalytic reactor at temperature range from 450 - 550 C and 30 - 90 seconds holding time. Analysis of variance (ANOVA) shows that only holding time play significant role in this study with Prob F of 0.0479 which is less than 0.05. The value of R square is 0.4994 shows there is only 49.94 bio - oil production depends on the chosen parameters. The functional groups in bio - oil were analyzed using Fourier Transform Infrared Spectroscopy (FTIR). The major compounds present in EFB pyrolytic bio - oil were alkanes, aldehydes, ketones, esters and alcohols. Copper oxide (CuO) catalyst was characterized using Scanning Electron Microscope (SEM) and X - ray Diffraction (XRD) to determine the morphology and the phase of the catalyst. SEM analysis showed that the CuO catalyst is cubical in shape with particle size in the range of 0.778 - 1.217 m. Analysis from XRD shows CuO is crystalline and identified as tenorite phase.